Nutrient Intake and Nutritional Status in Hungarian Gynecological Cancer Patients - Bárány, Beatrix; Póka, Róbert (Progress in Nutrition, 2021)
Aims: The incidence of malignant diseases is on the rise. Although nutrition and nutritional status do not get enough attention in the therapy of gynecological tumors, they may affect mortality and morbidity. More information on nutrient intake and nutritional status of gynecological cancer patients are needed to provide generalizable advice. The primary aim of our study was to analyze the nutrient intake, risk of malnutrition and quality of life among Hungarian gynecological cancer patients. Methods: We used a 3-day food record in order to assess energy and nutrient intake. The Malnutrition Universal Screening Tool was used to establish malnutrition risk, and the quality of life was evaluated using the EORTC-QLQ-C30 questionnaire. We included one hundred ninety-five gynecological oncology patients diagnosed with cervical, endometrial or ovarian cancer in our study. Results: Based on our results malnutrition risk affects 39% of gynecological oncology patients at the time of diagnosis, while this rate is considerably higher among patients under treatment. Furthermore, the intake of most micronutrients were less than the recommended dose, regardless of the status of the disease. Also, we found the quality of life to be strongly related to malnutrition risk. Conclusions: The study suggests that early detection of malnutrition risk and nutritional interventions are necessary among Hungarian gynecological cancer patients to helping improve nutrition intake, nutrition status and quality of life.